Development of an Integrated Accounting Information System with Point of Sale (POS) and Online Booking (Study Case: Coworking Space) - Putra, Victorio Almers Chrisetya; Pamudji, Andre Kurniawan; Kartin, Ang Prisilia (Soegijapranata Catholic University, 2024)
ABC Coworking Space Company is a service provider offering event space, meeting rooms, private offices, and coworking spaces for professionals. The company faces financial accounting challenges, particularly in recording sales transactions due to the limitations of the free Point of Sales (POS) system used, and complex, error-prone manual accounting processes. This research aims to develop an Accounting Information System (AIS) integrated with POS and online booking using the Rapid Application Development (RAD) method. The results show that the developed system minimizes inaccuracies in transaction recording, speeds up financial report preparation, and improves operational efficiency and customer satisfaction. The implementation of online booking features also successfully enhances the customer experience. With this new system, the company can manage sales, expenses, and financial reports in one integrated platform, significantly improving financial and operational management. Testing through User Acceptance Testing with the Blackbox method and interviews with front desk, finance staff, and customers indicates that the system meets user needs effectively.